Enacting Educational Philosophies: A Comparative Analysis of Islamic and Montessori Pre-School Paradigms in Practice - Nauratuddini Nauratuddini; Sekar Utami; Cintiya Elna Wibowo; Nur Cholimah; Nursyahirah Dayini binti Jafperi (Atfaluna: Journal of Islamic Early Childhood Education, 2026)
Purpose – This study examines how Islamic-based and Montessori-based early childhood educational philosophies are enacted through daily routines, teacher strategies, learning environments, and activities, while mapping the specific points of convergence and divergence between the two paradigms in practice. Design/methods/approach – This study employed a qualitative comparative case study design conducted at RA Al Marhamah and TK Hanacaraka Edukids Montessori School, Indonesia. Data were collected through direct observations, semi-structured interviews, and documentation involving two principals and two teachers. Data were analyzed using thematic analysis and cross-case comparison guided by Lickona’s moral education framework and Piaget’s theory of cognitive development. Findings – The findings generated four major themes. First, both institutions relied on daily habituation as the primary strategy for value internalization; however, the Islamic-based school emphasized collective worship, greetings, and religious routines, whereas the Montessori-based school emphasized Practical Life activities and autonomous participation. Second, teachers functioned as central moral agents, with Islamic teachers acting as moral and spiritual role models and Montessori teachers serving as facilitators of autonomy and self-regulation. Third, learning environments reinforced moral development through either explicit religious symbols and moral reminders or prepared environments that promoted responsibility and order. Fourth, both institutions encountered challenges in sustaining moral behavior, although behavioral consistency was more prominent in the Islamic setting, while emotional regulation and conflict resolution emerged as key challenges in the Montessori setting. Research implications/limitations – This study was limited to two early childhood education institutions and four key informants and focused primarily on school-based practices without incorporating parental or child perspectives, thereby limiting the transferability of the findings. Practical implications – The findings suggest that effective moral education may be strengthened by integrating the spiritual intentionality and explicit guidance characteristic of Islamic education with the autonomy-supportive and experiential learning environment of Montessori pedagogy through sustained school–family collaboration. Originality/value – This study provides a contextually grounded empirical comparison between independently established Islamic-based and Montessori-based early childhood education institutions in Indonesia. The findings demonstrate that structured spiritual guidance and experiential autonomy represent complementary pathways for fostering responsibility, empathy, respect, and moral self-regulation in early childhood.